Chronic Diarrhea Caused by Amebic Colitis and Inflammatory Bowel Disease - Hery Djagat Purnomo; Adjeg Tarius; Marcellus Simadibrata; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
The diagnosis of intestinal amebiasis is easily established based on colonoscopy, i.e. there is a specific characteristic of ulcer/lesion “discrete flask-shape ulcer” with normal mucosa among the ulcers. However, most patients with amebic colitis have non-specific clinical manifestations and their colonoscopy findings are hardly distinguished from inflammatory bowel disease. In the present case, the patient had a chief complaint of chronic bleeding diarrhea and abdominal pain. The fecal analysis found trophozoites of Entamoeba histolytica. Serology test (sero-amebic) revealed negative result. The colonoscopy examination reveals hyperemic mucosa, edema, and multiple ulcers with various sizes covered with fragile and easily bleed debris, from the rectum to ascending colon, rigid colon, narrowing lumen and tumor/mass appearance on ascending colon. The differential diagnosis was severe amebic colitis and inflammatory bowel disease. Based on the colonoscopy biopsy, we found an active chronic colitis along with dysplasia. The patient received management and treatment of severe amebic colitis and inflammatory bowel disease. Keywords: amebic colitis, bleeding diarrhea, fecal analysis, colonoscopy, biopsy, inflammatory bowel disease